ANALISIS PRODUK DOMESTIK BRUTO TERHADAP JUMLAH UANG BEREDAR DI ASEAN-5 - Intan Purnama, Sri; Dhea Lestari, Neng (Universitas La Tansa Mashiro, 2023)
This study aims to analyze the an influence of Gross Regional Domestic Product, Foreign Direct Investment (FDI), Inflation and Consumer Price Index (CPI) on the Money Supply in 5 Countries in ASEAN and within a period of 20 years from 2000 to 2019. Methods The analysis in this study uses the panel data method with the analysis model obtained is the ARDL (Autoregressive Distributed Lag) / PMG (Pooled Mean Group) Panel. The results showed that the variables of Gross Domestic Product, FDI, Inflation and CPI had a positive and significant an influence the Money Supply partially in the long run. Meanwhile, in the short term, the Gross Domestic Product variable has a positive and significant an influence on the Money Supply, FDI and CPI have a negative and significant effect on the Money Supply, and Inflation has a positive but not significant an influence on the Money Supply.